PENGARUH METODE PEMBELAJARAN DAN PERSEPSI TENTANG LINGKUNGAN TERHADAP KEPEDULIAN TARUNA PADA PELESTARIAN LAUT - Hadi Siswanto (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2010)
The research objectives are to determine the effect of learning method and environmental perception onawareness of marine conservation. The research was accomplished toward students of the Sekolah Tinggi IlmuPelayaran, Jakarta with factorial 2x2 design.The results are: (1) Awareness of marine conservation between on job trainning method and simulationtraining method have significant difference. (2) Students with higher of environmental perception, awareness ofmarine conservation between on the job training method and simulation training method have not significantdifference. (3) Students with lower of environmental perception, awareness of marine conservation between onthe job training method and simulation training method have not significant difference. (4) There is aninteraction effect between learning method and environmental perception on awareness of marine conservation.Therefore, in enhancing students’ awareness of marine conservation, using learning method and by controllingenvironmental perception should be taken in consideration.